Drying kinetics of Eggplant (Solanum Melongena L.) in an oven (Research, Society and Development, 2022)
Eggplant (Solanum melongena L.) is very beneficial to human health, but this fruit has a short shelf life, causing a limitation in its trade as a fresh product, requiring the investigation of processing methods that preserve its properties for longer. time. Therefore, the objective was to study the drying kinetics of eggplant in an oven with air current, at temperatures of 50, 60 and 70 ºC and to adjust mathematical models to the experimental data. Drying kinetics were determined by weighing the samples at regular intervals until the mass remained constant. With the drying data, the values of the water content ratio were determined and, later, the data were applied to different mathematical models. The Wang and Sing model was the one that best represented the experimental data for the three chosen temperatures, presenting the highest values of coefficient of determination and the lowest values ​​of mean square and chi-square deviation. Through the drying curves, it was observed that the higher the temperature, the shorter the process time, and the dry sample at a temperature of 70 ºC was the one that presented the best result, with a drying time of 270 min and 7.92 % moisture on a wet basis in the final sample. Therefore, the use of dried eggplant under these conditions becomes relevant, since it can be used later in the formulation of new food products, with a longer shelf life and with preserved nutritional properties.